Cloning and characterization of the str operon and elongation factor Tu expression in Bacillus stearothermophilus - Krásný, L; Vacík, T; Fucík, V; Jonák, J (Journal of bacteriology, 2000)
The complete primary structure of the str operon of Bacillus stearothermophilus was determined. It was established that the operon is a five-gene transcriptional unit: 5'-ybxF (unknown function; homology to eukaryotic ribosomal protein L30)-rpsL (S12)-rpsG (S7)-fus (elongation factor G [EF-G])-tuf (elongation factor Tu [EF-Tu])-3'. The main operon promoter (strp) was mapped upstream of ybxF, and its strength was compared with the strength of the tuf-specific promoter (tufp) located in the fus-tuf intergenic region. The strength of the tufp region to initiate transcription is about 20-fold higher than that of the strp region, as determined in chloramphenicol acetyltransferase assays. Deletion mapping experiments revealed that the different strengths of the promoters are the consequence of a combined effect of oppositely acting cis elements, identified upstream of strp (an inhibitory region) and tufp (a stimulatory A/T-rich block). Our results suggest that the oppositely adjusted core promoters significantly contribute to the differential expression of the str operon genes, as monitored by the expression of EF-Tu and EF-G.
Keywords: Geobacillus stearothermophilus; operon; Base Sequence; regulační geny; elongační faktor Tu; sekvence aminokyselin; bakteriální geny; Molecular Sequence Data; Operon; Amino Acid Sequence; genetické vektory; molekulární sekvence - údaje; Peptide Elongation Factor Tu; Cloning, Molecular; Genes, Regulator; sekvence nukleotidů; elongační faktor G; Genes, Bacterial; klonování DNA; promotorové oblasti (genetika); Promoter Regions, Genetic; Genetic Vectors; Peptide Elongation Factor G